MEDIA SOSIAL INSTAGRAM SEBAGAI RUANG EDUKASI LITERASI DAN PARTISIPASI PUBLIK PADA MAHASISWA INFORMATIKA POTENSI UTAMA - Egy Giovanny Bihaqqi; Nathalie Anastacia Simanjuntak; Bayu Adi Nugroho; Haliza Safira; Muhammad Azmi Aidil Wahid (Yayasan Formadana Tabagsel Indonesia, 2025)
The development of social media in the global era has transformed the way people interact, express opinions, and access information. Instigram is one of the social media platforms that has substantial influence due to its visual-based content and high level of user interaction. This study aims to examine the role of Instagram as an educational space in promoting digital literacy and enhancing public participation in social and national issues. The research method employed is a literature review by analyzing various national and international scholarly sources realted to digital literacy, public communication, and the use of Instagram. The findings indicate that Instagram function not only as a medium for communication and entertainment but also as a platform for learning and community empowerment through educational content, public discussions, and digital campaigns These activities encourage critical thinking, digital ethics, and active participation in online public space. However, challanges such as misinformation, algorithmic bias, and users limited ability to critically evaluate information remain significant barriers. Therefore, collaborative efforts among governments, educational institutions, and communities are necessary to strengthen an inclusive and responsible culture of digital literacy, particulary in the use of Instagram.